(untitled) (REMUNOM, 2024)
The present research generally aimed to: reflect on physical activity and health in elderly people in the Lhanguene elderly care center. From this perspective, the present research has as its theme: physical activity and health in the elderly: case study of the elderly care center in Lhanguene. Exploratory, descriptive and qualitative in nature. 21 subjects participated in this research, including 1 person responsible for the Lhanguene elderly care center and 10 elderly women and 10 men, aged between 50 and 70 years. An interview guide was used as a data collection instrument. The interview guide for the elderly and the person responsible for the lhanguene elderly care center. The analysis of the interviews carried out was based on content analysis, which was systematized. The research results obtained through reports from the two subgroups showed that there are programs a physical activity program for the good of the elderly, it is also concluded that the Lhanguene elderly care center adopts programs to help the elderly with physical activity and therefore, Because the study analyzed social and psychological gains for the elderly, it was found that the most recommended activities are those that lead the individual to meet other people. By discussing the authors’ main ideas regarding psychological and social effects, we found that the most recommended activities are: dancing, water aerobics, leisure and recreation activities (games, sports, board and card games, among others), walking and gymnastics.